Hubungan Perilaku Hidup Bersih dan Sehat (PHBS) dengan Kejadian Diare pada Balita - Christin Nawalia; Fitriani Ningsih; Lensi Natalia Tambunan (Jurnal Surya Medika (JSM), 2022)
Background: Infancy is the period most vulnerable to disease attacks. The disease that needs to be wary of attacking toddlers is diarrhea. Diarrhea is one of the environmental-based diseases that are the main cause of death and mortality. . Not carrying out indicators of clean and healthy living behavior (PHBS) is the cause of diarrhea in toddlers. One of the factors that influence the occurrence of diarrhea is a Clean and Healthy Life Behavior (PHBS). Not carrying out indicators of clean and healthy living behavior (PHBS) is the cause of diarrhea in toddlers, such as not giving exclusive breastfeeding to toddlers, not washing hands with soap, not using clean water, and not using healthy latrines. The purpose: In general, this study was to determine the relationship between Clean and Healthy Behavior (PHBS) with the incidence of diarrhea in children under five. Methode: literature review method, Google Scholar data source (2017-2020) articles using Indonesian. The Results: A total of 6 articles analyzed stated a relationship between clean and healthy living behavior (PHBS) and the incidence of diarrhea in toddlers. (p-value 0.000 <0.05). Conclusion: Based on 6 research articles, it is stated that there is a relationship between clean and healthy living behavior (PHBS) with the incidence of diarrhea in toddlers. One factor that influences diarrhea occurrence is the Clean and Healthy Life Behavior (PHBS). Not carrying out indicators of Clean and Healthy Living Behavior (PHBS) is the cause of diarrhea in toddlers, such as not giving exclusive breastfeeding to toddlers, not washing hands with soap, not using clean water, and not using healthy latrines.